2015
DOI: 10.1167/iovs.15-16778
|View full text |Cite
|
Sign up to set email alerts
|

ATF6Is Mutated in Early Onset Photoreceptor Degeneration With Macular Involvement

Abstract: Our results support ATF6 as a novel disease-causing gene for PRD and suggest that disrupted protein quality control mechanisms may be a novel pathological mechanism underlying human retinal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 25 publications
6
50
0
Order By: Relevance
“…Since LCA and RP are rare Mendelian disorders, variants with a frequency higher than 1/200 (for a recessive model) or 1/1000 (for a dominant model) were filtered out. After frequency-based filtering, we filtered out synonymous variants, identified known retinal disease-causing variants and predicted the pathogenicity of variants using SIFT (Ng and Henikoff 2003), Polyphen2 (Adzhubei et al 2010), LRT (Chun and Fay 2009), MutationTaster (Schwarz et al 2010), MutationAssessor (Reva et al 2011) as previously described (Wang et al 2014; Xu et al 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Since LCA and RP are rare Mendelian disorders, variants with a frequency higher than 1/200 (for a recessive model) or 1/1000 (for a dominant model) were filtered out. After frequency-based filtering, we filtered out synonymous variants, identified known retinal disease-causing variants and predicted the pathogenicity of variants using SIFT (Ng and Henikoff 2003), Polyphen2 (Adzhubei et al 2010), LRT (Chun and Fay 2009), MutationTaster (Schwarz et al 2010), MutationAssessor (Reva et al 2011) as previously described (Wang et al 2014; Xu et al 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Pre-capture Illumina libraries were generated as in previous literature. [21][22][23] The targeted DNA was captured, washed, and recovered using Agilent Hybridization and Wash Kits (Agilent Technologies). WES was performed by capturing the DNA with the NimbleGenSeqCap EZ Hybridization and Wash kit.…”
Section: Whole-exome Sequencing and Bioinformatic Analysismentioning
confidence: 99%
“…Using next-generation whole-exome sequencing, we recently discovered autosomal recessive mutations in the activating transcription factor 6 (ATF6) gene in patients with achromatopsia (1). ATF6 mutations span the entire coding region and include missense, nonsense, splice site, and single-nucleotide deletion and duplication changes (1)(2)(3). We previously showed that a missense mutation that introduced an arginine-to-cysteine substitution at amino acid residue 324 of the ATF6 protein compromised ATF6 activity in patient fibroblasts obtained from an achromatopsia family (1).…”
mentioning
confidence: 99%